2015
DOI: 10.1093/hmg/ddv118
|View full text |Cite
|
Sign up to set email alerts
|

Non-syndromic retinitis pigmentosa due to mutations in the mucopolysaccharidosis type IIIC gene, heparan-alpha-glucosaminide N-acetyltransferase (HGSNAT)

Abstract: Retinitis pigmentosa (RP), the most common form of inherited retinal degeneration, is clinically and genetically heterogeneous and can appear as syndromic or non-syndromic. Mucopolysaccharidosis type IIIC (MPS IIIC) is a lethal disorder, caused by mutations in the heparan-alpha-glucosaminide N-acetyltransferase (HGSNAT) gene and characterized by progressive neurological deterioration, with retinal degeneration as a prominent feature. We identified HGSNAT mutations in six patients with non-syndromic RP. Whole e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 37 publications
8
58
2
Order By: Relevance
“…A similar tissue-dependent activity-effect model was also suggested for other genes, for instance CLN3, CEP290, HGSNAT and MFSD8 that can be associated with syndromic and non-syndromic retinal diseases. [28][29][30][31] The hypothesis that the missense variants in the WD40 domain do not completely abolish Jouberin function is further supported by our observation that cultured fibroblasts of patient A-II:1 (c.2174G>A and c.2258A>T) had no disrupted cilium formation, while Tuz et al showed that mutations in individuals with JBTS cause impaired ciliogenesis in patient's fibroblasts. 27 Additionally, we did not observe mislocalisation of either IFT-B (IFT88) or IFT-A (WDR19), a phenotype that was previously detected in other severe ciliopathies.…”
Section: Discussionsupporting
confidence: 63%
“…A similar tissue-dependent activity-effect model was also suggested for other genes, for instance CLN3, CEP290, HGSNAT and MFSD8 that can be associated with syndromic and non-syndromic retinal diseases. [28][29][30][31] The hypothesis that the missense variants in the WD40 domain do not completely abolish Jouberin function is further supported by our observation that cultured fibroblasts of patient A-II:1 (c.2174G>A and c.2258A>T) had no disrupted cilium formation, while Tuz et al showed that mutations in individuals with JBTS cause impaired ciliogenesis in patient's fibroblasts. 27 Additionally, we did not observe mislocalisation of either IFT-B (IFT88) or IFT-A (WDR19), a phenotype that was previously detected in other severe ciliopathies.…”
Section: Discussionsupporting
confidence: 63%
“…Suzki et al have highlighted the extremely rare association between RP and MPSII, and a more recent study has shown that the disease gene for MPSIIIC (HGSNAT) can cause a nonsyndromic form of RP. 25,26 It appears likely that the homozygous truncating mutation we identified in GNS is causal for both MPS and RP within this extended family, although we cannot exclude the remote possibility that it is present in tight linkage disequilibrium with another mutation causing RP.…”
Section: Discussionmentioning
confidence: 83%
“…The HGSNAT (heparan-alpha-glucosaminide Nacetyltransferase) gene encodes a lysosomal acetyltransferase, which is one of several enzymes involved in the lysosomal degradation of heparin sulfate. Mutations in this gene are associated with Sanfilippo syndrome type C (mucopolysaccharidosis) and retinitis pigmentosa [Canals et al, 2011;Haer-Wigman et al, 2015]. FNTA (farnesyltransferase) is a protein-encoding gene related to apoptotic cleavage of cellular protein.…”
Section: Discussionmentioning
confidence: 99%